Implementasi Freeradius pada Jaringan Hotspot dengan Mikrotik dan MySQL - Setyo Abdi Nugroho; Herdianto Herdianto; Hendry (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
A computer network is a collection of devices connected to communicate and exchange data. The internet is a global network that connects users worldwide. To access the internet, Mikrotik network devices and LAN cables are commonly used. However, LAN cables are less efficient for multiple users, especially smartphone users, as Android devices do not support LAN connections. Mikrotik offers a hotspot feature that allows users to connect wirelessly. To ensure security and prevent unauthorized access, login authentication is required. This can be achieved by integrating the RADIUS feature on Mikrotik with FreeRADIUS and MySQL on an Ubuntu server. User accounts for authentication can be managed through the daloRADIUS web application. The integration of FreeRADIUS, MySQL, and daloRADIUS with Mikrotik simplifies user account management and prevents unauthorized users from accessing the network. This system enhances security and ensures only registered users are able to access the internet via the hotspot